The IMBPC HVAC system: Wireless Sensors and IoT Platform. Issue 10 (2018) - Silva, S.; Ruano, A.
Abstract: Model Based Predictive Control (MBPC) is perhaps the most proposed technique for HVAC control, since it offers an enormous potential for energy savings. Despite the large number of papers in this topic during the last years, there are only a few reported applications of the use of MBPC for existing buildings, under normal occupancy conditions and, to the best of our knowledge, no commercial solution yet. A marketable solution has been recently presented by the authors, coined IBMPC HVAC system. This paper focuses on two components of this integrated system, the Self-Powered Wireless Sensors and the IoT platform developed.